Phthalocyanines and Some Current Applications - Yilmaz, Yusuf (IntechOpen, 2017)
Since their initial accidental synthesis and characterization in Scotland in the late 1920s, there has been a strong research focus on the use of phthalocyanines (Pcs) as dyes and pigments. In recent years, active research fields have included their use in electrophotography, photovoltaic and solar cells, molecular electronics, Langmuir-Blodgett films, photosensitizers, electrochromic display devices, gas sensors, liquid crystals, low-dimensional conductors, and optical disks. Phthalocyanines possess interesting biological, electronic, optical, catalytic, and structural properties. The main disadvantage is their insolubility in common solvents due to strong intermolecular - interactions. The solubility of phthalocyanines can be increased by various methods such as the formation of anionic and cationic species and both axial and peripheral substitution. Substitution at the nonperipheral and peripheral positions of the benzo moieties usually enhances their solubility in organic solvents. The most important advantage of phthalocyanines compared to porphyrins is that their Q bands lie at longer wavelengths and are considerably more intense. In this book, you will find synthesis and some applications of various phthalocyanine derivatives.